Monofunctional Cities: Problems, Support Provision and Development - Kuzmenko, L.M.; Soldak, M.O. (Економічний вісник Донбасу, 2010)
The paper considers the peculiarities of industry in the monoindustrial cities in Donetsk region. The actions for solving the problems of the social and economic development are proposed here. Key words: monofunctional (monoindustrial) city, development, industry, state management, regional policy. У статті розглянуто особливості промисловості моногалузевих міст Донецької області. Запропоновано заходи, що стосуються вирішення проблем їх соціально-економічного розвитку. Ключові слова: монофункціональне (моногалузеве) місто, розвиток, промисловість, державне управління, регіональна політика. В статье рассмотрены особенности промышленности моноотраслевых городов Донецкой области. Предлагаются мероприятия по решению проблем их социально-экономического развития. Ключевые слова: монофункциональный (моноотраслевой) город, развитие, промышленность, государственное управление, региональная политика.